Institutionalization of older people: prediction and prevention. (April 2011) - Brown, Siobhan HM; Abdelhafiz, Ahmed H
Expenditure on long-term care is likely to increase with the aging of the population and the increased need for institutionalization. Identifying risk factors for nursing home admission is of particular interest to develop predictive tools and intervention programs to reduce entry into nursing homes. Most of the patient-related risk factors leading to nursing home admission are based on an underlying decline in physical and/or cognitive functions. Interaction between caregiver and care recipient characteristics is also an important contributing factor. Structured preventive programs are more effective than individual counseling. Tailoring intervention programs to individual needs and preferences, continuous and comprehensive support of patients and their caregivers with access to a geriatrician is an important factor in the success of an intervention. Further research is still required to explore whether interventions at early stages of chronic diseases would delay physical and cognitive dysfunction and reduce the institutionalization of older people.